Eu não movo guerra ao Catolicismo: Contribuiçoes de Tavares Bastos para a construção da liberdade religiosa no Brasil Imperial, a partir da obra Cartas do Solitário - Chavante, Esdras Cordeiro; Rocha, Ivan Esperança (Universidade Estadual de Maringa, 2015)
Aureliano Cândido Tavares Bastos was one of the protagonists in the debate on the possibility of religious freedom in 19th century Brazil. Current paper analyzes the book Cartas do Solitário and Bourdieu field concept to have an in-depth discussion on the issue and other questions of interest.
I am not warring against Catholicism: The contributions of Tavares Bastos for religious freedom in Imperial Brazil in his book Cartas do Solitário
Keywords: Citizenship; Civil Rights; History of Religions; Religious freedom; Tavares Bastos